1990
DOI: 10.1037/0022-3514.59.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Gender and social structure in the demand/withdraw pattern of marital conflict.

Abstract: This study examined the effects of gender and social structure on the demand/withdraw pattern of marital conflict. In this pattern, the demander, usually the woman, pressures the other through emotional requests, criticism, and complaints, and the withdrawer, usually the man, retreats through defensiveness and passive inaction. In this study, 31 couples were assessed in 2 conflict situations: 1 in which husband wanted a change in wife and 1 in which wife wanted a change in husband. Data from husbands, wives, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

66
704
6
10

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 641 publications
(786 citation statements)
references
References 11 publications
66
704
6
10
Order By: Relevance
“…Kelley and his colleagues concluded that men are indeed conflict-avoidant; they find it upsetting to deal with emotional problems. Women are conflict-confronting; they are frustrated by men's avoidance and ask that the problem and the feelings associated with it be confronted (see Canli, Desmond, Zhao, & Gabriell, 2002;Christensen & Heavey, 1990;Gottman & Krokoff, 1989;Gottman & Levenson, 1988;Kiecolt-Glaser, 1998;Notarius & Johnson, 1982;Schaap, 1982; for similar results. )…”
mentioning
confidence: 62%
“…Kelley and his colleagues concluded that men are indeed conflict-avoidant; they find it upsetting to deal with emotional problems. Women are conflict-confronting; they are frustrated by men's avoidance and ask that the problem and the feelings associated with it be confronted (see Canli, Desmond, Zhao, & Gabriell, 2002;Christensen & Heavey, 1990;Gottman & Krokoff, 1989;Gottman & Levenson, 1988;Kiecolt-Glaser, 1998;Notarius & Johnson, 1982;Schaap, 1982; for similar results. )…”
mentioning
confidence: 62%
“…Belsky et al (1984) and Lamb and Elster (1985) also found that fathers' engagement with their children was related to the quality of the marital relationship, but, at the same time, they found little relation between the level of marital interaction (e.g., degree of communication) and mothers' involvement with their children. Basically, it appears that marital conflict results in the fathers' withdrawal--emotional or physical from his children and his spouse (see, e.g., Christensen & Heavey, 1990). However, this withdrawal is sometimes more pronounced for daughters than for sons (Kerig, Cowan, & Cowan, 1993) and varies with the nature of the interpersonal dynamics between husband and wife (Gottman, 1998).…”
Section: Genetic Social and Development Correlatesmentioning
confidence: 99%
“…However, demand and withdraw behaviors have been of particular concern because of their (a) frequent presence in distressed couples (Christensen & Shenk, 1991), (b) link with declines in relationship satisfaction over time (Heavey, Christensen, & Malamuth, 1995), and (c) link to spousal abuse (Berns, Jacobson, & Gottman, 1999). In addition, studies consistently show that women express more demands and men exhibit more withdrawal during problem-solving discussions (e.g., Christensen & Heavey, 1990;Gottman & Krokoff, 1989;Heavey, Layne, & Christensen, 1993;Vogel & Karney, 2002). This sex difference in problem-solving behaviors spurred interest in why these differences in behavior exist.…”
mentioning
confidence: 99%